(untitled) (Third Sector Social Economic Review, 2023)
Work accidents are a significant issue globally and in our country, posing a crucial concern for all sectors, with the construction industry particularly ranking high in this regard. Especially in a report prepared after the Chernobyl Disaster, it was concluded that accidents were not only due to technical issues but also resulted from workers’ unsafe behaviors. Consequently, safety culture and occupational safety performance have become priority areas for research. This study aimed to investigate the occupational safety performance and risk-taking behaviors of workers in metro construction projects, where occupational health and safety (OHS) risk factors are abundant within the Turkish construction industry. To this end, a survey was conducted with employees of three ongoing metro projects in Istanbul. The survey forms, prepared online, were delivered to the employees by the OHS managers of the projects. A total of 129 surveys were returned. The data were tested using SPSS and Lisrel software. The analysis revealed relationships between the sub-dimensions of occupational safety performance, namely safety compliance and safety participation, and participants’ risk-taking behaviors. Additionally, based on confirmatory factor analysis in structural equation modeling, path coefficients for all items were found to be statistically significant.